(untitled) (American Journal of Islam and Society, 2013)
Understandably, Muslims tend to bristle at the common quip by non-Muslims (especially in the West) that Islam is badly in need of a “Reformation” – referring to the sixteenth-century Protestant Reformation that, despite the violence it unleashed in Europe for the next two centuries, did actually engender some positive changes within the Catholic church. No people, regardless of who they are or where they live, like outsiders telling them that they need to set their house in order. This book, by contrast, is written by an insider telling other insiders (Muslims) that Islamic law needs serious revamping, a weighty charge indeed. The author faces an extra hurdle based on the fact that he does not belong to the traditional ulama class, the gatekeepers of Islamic jurisprudence. Farooq earned a Ph.D. in economics at the University of Tennessee, taught in the United States for over a decade, and now heads the Bahrain Institute for Banking and Finance’s Centre for Islamic Finance. Rashid Rida would have said in his day that Farooq represents the new face of the ulama: one well versed in many aspects of the Islamic sciences and yet, because of his parallel expertise in the modern sciences, one who could provide indispensable guidance to society in the name of Islam. Why does Islam need a reformation? Much of the book seeks to expose the abuse, misapplication, and distortion of the Shari‘ah committed by states and individual ulama alike, for it “is being used to rubber stamp extremist, violent behavior, the abuse of women, and the unfair control and imprisonment of human beings” (p. 16). Speaking of South Asia in particular, he writes that the following are “prevalent”: “[t]he torture and persecution of brides over their dowry, the throwing of acid onto girls who do not either want to accept a proposal of marriage or to concede to extramarital sex, the practice of honor killings and so on …” (p. 86) ...